Body image and sexual life satisfaction in women considering female genital cosmetic surgery in Iran - Setareh Derakhshanpour; Fatemeh Bagheri; Fatemeh Rahmanian; Seyede Zahra Jafari; Zahra YazdanPanahi (Journal of Health, Population and Nutrition)
Abstract Background Further attention to genital organs has become a concern for women in line with changes in society’s culture. In recent years, the number of surgeries has grown increasingly. The aim of this study was to investigate the relationship between body image and satisfaction with sexual life of female genital cosmetic surgery volunteers in reproductive age women in Shiraz. Methods This cross-sectional study was performed on 160 women referring to Shiraz Health and Medical Centers willing to undergo female genital cosmetic surgery. Data collection was performed using Demographic Information Questionnaire, SWBI and Enrich Marital Satisfaction Questionnaire. The data were analyzed through Spss24 software using Pearson statistical methods of correlation coefficient and one-sample t-test. Results This cross-sectional study was conducted on 160 women (average age of 30.83 ± 5.48) willing to undergo genital cosmetic surgery at Shiraz health and medical centers. The results of this study showed that women willing to undergo female genital cosmetic surgery are satisfied with their physical appearance. Correlation coefficient test between body image and satisfaction with marital life also showed that there is a significant relationship between these two variables (p < 0.001). This means that with the satisfaction of body image, the level of satisfaction with marital life also increases. Conclusion The most important findings of this study included no correlation between women’s negative perceptions of their bodies and dissatisfaction with sexual life with a tendency to cosmetic surgery on the genital area. Therefore, it is necessary to understand the factors influencing this decision.